Strategi Pemberdayaan UMKM Pangan Dapur Sehat Binaan Baitul Maal Muamalat di Kebon Waru Bandung - Lasmanah, Lasmanah; Nurrachmi, Intan; Rukmana, Jaka; Zaeni, Mutiara Refanisa; Fitriyanti, Asti (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Food MSMEs have a strategic role in encouraging local economic growth, increasing food security, and creating jobs. However, many food MSME actors, including the Baitul Maal Muamalat Healthy Kitchen in Kebon Waru Village, Bandung, face challenges in the aspect of product innovation, namely low product durability due to suboptimal food preservation and packaging methods, thus hindering the distribution of products to a wider market. In addition, the lack of halal certification for some members causes limitations in reaching a wider market segment. This program aims to formulate an effective empowerment strategy to increase the capacity and competitiveness of healthy kitchen MSMEs in terms of product preservation and packaging, as well as business sustainability management. The methods used include a qualitative approach with field observations, in-depth interviews with MSME actors and Baitul Maal Muamalat managers, as well as participatory and applicative approaches. The results show that empowerment based on continuous mentoring, product innovation training, and halal certification assistance are able to increase knowledge about product preservation techniques, improve production management and awareness of the importance of halal certification. Based on the results of the pretest conducted before the training, the partner's knowledge of food preservation techniques obtained an average score of 68.9, while the posttest results conducted after the training obtained an average score of 89.4, which shows an increase in ability of 20.5% in terms of knowledge of food preservation and packaging techniques. An empowerment strategy that is integrated with a participatory approach and institutional support can encourage the independence and sustainability of food MSMEs.ABSTRACUMKM pangan memiliki peran strategis dalam mendorong pertumbuhan ekonomi lokal, meningkatkan ketahanan pangan, dan membuka lapangan kerja. Namun, banyak pelaku UMKM pangan, termasuk Dapur Sehat binaan Baitul Maal Muamalat yang berada di Kelurahan Kebon Waru, Bandung, menghadapi tantangan dalam aspek inovasi produk yaitu rendahnya daya tahan produk akibat metode pengawetan dan pengemasan makanan belum optimal, sehingga menghambat distribusi produk ke pasar yang lebih luas. Disamping itu, belum adanya sertifikasi halal bagi sebagian anggota menyebabkan keterbatasan dalam menjangkau segmen pasar yang lebih luas. Program ini bertujuan untuk merumuskan strategi pemberdayaan yang efektif untuk meningkatkan kapasitas dan daya saing UMKM Dapur sehat dalam hal pengawetan dan pengemasan produk, serta manajemen keberlanjutan usaha. Metode yang digunakan meliputi pendekatan kualitatif dengan observasi lapangan, wawancara mendalam terhadap pelaku UMKM dan pengelola Baitul Maal Muamalat, serta pendekatan partisipatif dan aplikatif. Hasilnya menunjukkan bahwa pemberdayaan berbasis pendampingan berkelanjutan, pelatihan inovasi produk, dan pendampingan sertifikasi halal mampu meningkatkan pengetahuan tentang teknik pengawetan produk, memperbaiki manajemen produksi dan kesadaran pentingnya sertifikasi halal. Berdasarkan hasil pretest yang dilakukan sebelum pelatihan bahwa pengetahuan mitra tentang teknik pengawetan makanan didapatkan skor rata-rata 68,9, sedangkan hasil postest yang dilakukan setelah pelatihan didapatkan skor rata-rata 89,4, hal tersebut menunjukkan peningkatan kemampuan sebesar 20,5% dalam hal pengetahuan teknik pengawetan dan pengemasan makanan. Strategi pemberdayaan yang terintegrasi dengan pendekatan partisipatif dan dukungan kelembagaan dapat mendorong kemandirian dan keberlanjutan UMKM pangan.